Classification of Bus Driving Behaviour In Universiti Malaysia Sabah Campus - Elsa Eka Putri; Lillian Gungat; Dewi Nur Atieqah Binti Baharun Alam (Sainstek (e-Journal), 2021)
Driving behaviour has been studied by numerous researchers for the past few years. It includes the instantaneous driving behaviour observations and the drivers speed which are said to be influenced by many factors, such as the demographic measure of the drivers, environmental, passenger effect, and road characteristics. This paper describes the recent analysis and classification of driver behaviour in actual driving scenarios among the bus drivers in Universiti Malaysia Sabah (UMS) Main Campus, Kota Kinabalu. This research focussed on determining the riderships of bus in UMS campus, to investigate the differences of instantaneous driving behaviours of bus drivers during the acceleration phase when leaving bus stops, and to poduce the classification of the bus driving behaviour in UMS based on the driver’s accelerations. In order to achieve the objective of this study, observations were made for determining the riderships and the differences in instantaneous bus driving behaviour several times for each bus stops. For drivers speed and accelerations, a mobile applications called Speedometer GPS was used to obtain the data. Interview was conducted to a total number of 10 respondents to obtain their demographic measure. The results obtained shows the ridership of UMS bus is the highest in the afternoon peak. The instantaneous driving behaviour produce the head movement as the highest percentage during peak hour, and inattentive behaviour as the highest during the off peak hour. The bus drivers in UMS were classified as Aggressive and Calm Behaviour Category.